An Evaluation of the Rotator Cuff Repair Research Pipeline. Issue 11 (14th November 2018) - Checketts, Jake X.; Scott, Jared; Gordon, Josh; Jones, Jaclyn; Horn, Jarryd; Farabough, Michelle; Whitener, Jake; Boose, Marshall; Vassar, Matt
Background: We conducted a study of recommendations from the American Academy of Orthopaedic Surgeons (AAOS) guideline, "Optimizing the Management of Rotator Cuff Problems." Using these recommendations, we conducted searches of clinical trial registries and bibliographic databases to note the extent to which new research has been undertaken to address areas of deficiency. Hypothesis: Newly conducted research regarding rotator cuff repair and injury is available that will fill knowledge gaps identified by the AAOS guideline. Study Design: Cross-sectional study. Methods: For each recommendation in the AAOS guideline, we created PICO (participants, intervention, comparator, outcome) questions and search strings. Searches were conducted ofClinicalTrials.gov, the World Health Organization's International Clinical Trials Registry Platform, MEDLINE via PubMed, and EMBASE to locate studies undertaken after the final literature search performed by the AAOS work group. Results: We located 210 newly registered trials and 448 published studies that are relevant to the recommendations made in the rotator cuff guideline. The majority of the recommendations have been addressed by relevant registered trials or published studies. Of the 448 published studies, 185 directly addressed the guideline recommendations. Additionally, 71% of the 185 published studies directly addressing the recommendations were randomized trials or systematic reviews/meta-analyses. The most important finding of our study was that the recommendations in the AAOS rotator cuff guideline have been adequately addressed. Conclusion: Orthopaedic researchers have adequately addressed knowledge gaps regarding rotator cuff repair treatment and management options. As such, the AAOS may consider a guideline update to ensure that recommendations reflect current findings in orthopaedic literature.